Depinning process of magnetic domain walls in cylindrical nanowires with a chemical constraint. (9th February 2017) - Castilla, D; Maicas, M; Prieto, J L; Proenca, M P
Abstract: In this work we have studied with micromagnetic simulations the pinning process of a magnetic domain wall (DW) travelling in a cylindrical magnetic nanowire with a section where the composition has been altered with respect to the rest of the nanowire (chemical constraint). We have studied the depinning process for a non-magnetic, a paramagnetic and a ferromagnetic constraint and we show that the pinning strength in this type of defect can be tailored by a change of composition. The ferromagnetic chemical constraint is the strongest pinning site but it can stop the DW only when there is a significant reduction of the exchange energy and the saturation magnetization with respect to the rest of the wire. Chemical constraints may constitute a promising alternative to geometrical constraints in some devices such as the race-track memory.